Pharmacokinetic Changes and Dosage Adjustment of Digoxin in Elderly Patients with Atrial Fibrillation: A Narrative Review - Alfaqeeh, Mohammed; Permatasari, Lanny I.; Khairinisa, Miski A.; Rusdiana, Taofik (Universitas Padjadjaran, Indonesia, 2023)
Digoxin is a cardiac glycoside medication commonly used to control rapid heart rates in Atrial Fibrillation (AF). However, digoxin has a narrow therapeutic range and can be associated with adverse effects, including increased mortality risk, especially in the elderly. Pharmacokinetic changes occur with aging, affecting the way drugs are absorbed, distributed, metabolized, and eliminated from the body. Thus, this narrative review aimed to assess the optimization of digoxin dosing in elderly patients with AF while considering pharmacokinetic changes due to aging. We performed a comprehensive computerized search of relevant English articles and a manual examination of reference lists from primary sources formed the basis of this scoping review. This involved an extensive computerized search of relevant articles in English and a manual search of the reference lists of original articles. The review highlighted the need to carefully monitor digoxin levels in elderly patients due to changes in body composition, protein binding, hepatic clearance, renal excretion, and other factors affecting drug metabolism. Furthermore, we summarized guidelines and recommendations for optimizing digoxin dosing in elderly patients with AF. By shedding light on the intricacies of optimizing digoxin dosing in the elderly with atrial AF and emphasizing the significance of accounting for age-related pharmacokinetic changes, this review offers valuable insights for healthcare practitioners and researchers in the field. Addressing these aspects is crucial to enhancing therapeutic outcomes and minimizing potential risks associated with digoxin therapy in this vulnerable patient population